PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2023 - Daffa Shafira Choirunnissa; Dewi Puji Rahayu; Yanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of profitability, leverage, liquidity, and firm size on tax aggressiveness in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2016–2023 period. This research uses a quantitative approach with a descriptive method. The data used are secondary data obtained from financial statements and annual reports. The data analysis technique employed is multiple linear regression using SPSS version 27.0. The results show that partially, profitability, leverage, and liquidity have a significant effect on tax aggressiveness, while firm size has no significant effect. Simultaneously, all independent variables significantly influence tax aggressiveness. The Adjusted R Square value of 0.347 indicates that the independent variables explain 34.7% of tax aggressiveness, while the remaining 65.3% is influenced by other variables outside the research mod